Pengembangan E-Modul Berbasis PMRI pada Materi Segi Empat - Mandasari, Novianti; Kusnanto, R. Angga Bagus (Jurnal Pendidikan Matematika : Judika Education, 2024)
This research aims to develop an e-module product based on PMRI on class VII quadrilateral material, Class VII SMP IT AN-NIDA Lubuklinggau in accordance with the 2013 curriculum and to produce an e-module that is valid, practical and has potential effects. This development research method uses the ADDIE (Analysis-Design-Develop-Implement-Evaluate) development model. The research was conducted at AN-NIDA Lubuklinngau IT Middle School so that the population and sample or research subjects were class VII students with a total of 28 students. Data collection techniques in this research used interviews, questionnaires and tests. The research results show that the data analysis technique uses the validity of language experts with a value of 0.75, media experts with a value of 0.72 and material experts with a value of 0.68, so that the results of the analysis of the three validators get a value of 0.71 in the valid category. Furthermore, the analysis of the practicality of teachers and students received a score of 92.07% in the very practical category and had a potential effect of 92.85%. So it can be concluded that the PMRI-based e-module on class VII quadrilateral material for Class VII SMP IT AN-NIDA Lubuklinggau has met the criteria of being valid, practical and having potential effects. Keywords: E-module, PMRI, Quadrilateral Material